Synthesis, Characterization and Antibacterial and Antifungal Evaluation of Some Para-Quinone Derivatives - Amani, A. M. (Drug Research, 2014)
Some novel Pyrrolo [2,3-f] Indole-3,7-Dicarbonitrile derivatives (1–5) were synthesized using chloranil, malononitrile and anilines. The structures of the newly synthesized compounds were characterized by elemental analysis, FT-IR, 1H- and 13C-NMR and mass spectroscopy. These compounds were screened for in vitro antibacterial and antifungal activities against some human pathogenic micro-organisms by employing the disc diffusion technique. Some of the compounds showed moderate to good biological activities when compared with standard drugs.
Keywords: quinones; pyrrolo[2,3-f]indole Dicarbonitrile; biological evaluation; synthesis